Design and Development of an Immersive Game-Based Mandarin Language Learning Medium to Enhance Student Learning Motivation - Nuskha Ilma Arini (Unversitas Muhammadiyah Mataram, 2025)
The rapid advancement of technology in the Industrial Revolution 4.0 era has driven innovation in education, particularly through the use of interactive digital learning media. This study aims to develop an immersive game-based learning media for Mandarin language instruction using the Roblox Studio platform to enhance students’ motivation and engagement in the learning process. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The analysis phase identified that Mandarin learning tends to be monotonous and less engaging for students. Validation results from content experts reached 83% and media experts 81%, both categorized as good. User testing yielded 84%, while small-group and large-group trials achieved 88% and 85%, respectively, categorized as very high. The developed learning game integrates coin hunt and leaderboard features that effectively create an interactive and competitive learning experience. Overall, the findings indicate that the game-based learning media is feasible, engaging, and effective in improving students’ motivation and learning outcomes in Mandarin language courses within vocational higher education.